Professor Jamal Nazrul Islam: The Scientist Wandering in Theoretical Science, Astronomy, and Cosmology - Kamrujjaman, Md (GANIT: Journal of Bangladesh Mathematical Society, 2022)
Abstract not available GANIT J. Bangladesh Math. Soc. 42.1 (2022) 001- 009